Law Enforcement in the Perspective of Legal Sociology - Burhanuddin Burhanuddin; Wahyuniar Wahyuniar; Maskawati Maskawati (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This paper examines the effectiveness of law enforcement in society from the perspective of legal sociology. The goal is to explain the extent to which law enforcement can be effective in society. To obtain data from the problem, the author uses the library research method to collect information relevant to the topic or problem to be studied. The type of data used in this study is secondary data obtained from library materials or literature that have a relationship with the object being studied. The results of the study show that the effectiveness of law enforcement has not been maximized. This is marked by the fact that it is not easy for the law to be enforced in cases involving elites or officials. The law should apply to all circles, not recognizing social stratification in its enforcement, but the reality that occurs is inversely proportional to the principle of law, the law is used as a tool for those who have interests. Therefore, the sociology of law is present to examine the impact of the enactment of a law in society, so that social phenomena can arise and develop in society. The sociology of law and the effectiveness of law are very closely related, because what will be discussed in the sociology of law will not be separated from the assessment of how far the effectiveness of law exists in society as part of social phenomena.